MODEL SUPPLY CHAIN OPERATION REFERENCE SEBAGAI PENINGKATAN KINERJA INDUSTRI TAHU KUNING DI KEDIRI - Indrasari, Lolyka Dewi; Yudha Tripariyanto, Afiff; Komari, Ana; Hidayat, Andrean Pradana; Swardana, Emilia (KAIZEN : Management Systems & Industrial Engineering Journal, 2023)
The purpose of this study is to assess the comparative performance of the yellow tofu industry supply chain from MJS, WK and PM Kediri to improve the role of the Supply Chain Operation Reference model. The stage of this study is to assess the instrument of the Supply Chain Operation Reference with the weighting that has been planned percentage value. The findings achieved are the Supply Chain Response Time instrument with an estimated time of 7 days each; 5 days; and 6 days with actual achievements with a time of 9 days each; 8 days; and 9 days. The best Leadtime Order Fulfillment Instrument is MJS with Best in Class criteria with an achievement of < 4 days; Weka with the achievement of 5 days; and PM with 4 days of achievement. The contribution achieved is to achieve Advantage and Best in Class from the method used. Keywords: Performa, Supply Chain Operation Reference, Tahu Kuning ABSTRAK Tujuan penelitian ini adalah menilai performa perbandingan rantai pasokan industry tahu kuning dari MJS, WK dan PM Kediri untuk meningkatkan peran model Supply Chain Operation Reference. Tahapan penelitian ini adalah menilai instrumen dari Supply Chain Operation Reference dengan pembobotan yang telah direncakan nilai prosentase. Temuan yang dicapai yaitu instrumen Supply Chain Response Time dengan estimasi waktu masing – masing target sebesar 7 hari; 5 hari; dan 6 hari dengan aktual pencapaian dengan waktu masing – masing 9 hari; 8 hari; dan 9 hari. Instrumen Order Fulfillment Leadtime terbaik adalah MJS dengan kriteria Best in Class dengan pencapaian < 4 hari; Weka dengan pencapaian 5 hari; dan PM dengan pencapaian 4 hari. Kontribusi yang dicapai adalah mencapai Advantage dan Best in Class dari metode yang dipakai. Keywords: Performa, Supply Chain Operation Reference, Tahu Kuning